Bienes y servicios ambientales del estrato arbóreo para estrategias de conservación en el lote 1 de CIIDEA - Loor Rosado, Gerardo Rogelio (2024)
The main objective of this research work was to establish the environmental goods and services of the tree layer for conservation strategies in CIIDEA lot 1. In order to carry out this objective, a non-experimental type of research was carried out with a descriptive scope and a mixed approach, which is to say, both qualitative and quantitative approaches were used. The methods used were bibliographic, field, analytical and descriptive, including observation and interview techniques. The work was divided into three phases; The first phase included a diagnosis of the study area, showing that it is a forest with little intervention, as there is no contamination index. However, in certain sectors, tree felling was evident, accounting for a total of 2224 individual trees distributed in 17 families, where the species with the highest importance value index (IVI) were guachapelí (68.05%), guasmo (62.88%), carob (26.04%) and samán (21.32%). The next phase was the determination of the environmental goods and services of the tree stratum where the sociability of the species with agroforestry systems, phytoremediation potential, nutrient fixation and biodiversity conservation were highlighted, followed by carbon sequestration, provision of food for fauna, provision of traditional medicine, soil conservation, fuel wood and handicraft confections. Finally, a proposal was made for the environmental conservation of the goods and services identified in the area in order to contribute to the mitigation of the impacts currently generated by climate change.